Analisis Yuridis terhadap Kebijakan Pengembangan Energi Hijau Perspektif Hukum Lingkungan dan Pengelolaan Berkelanjutan Di Indonesia - Siti Nur Hodijah; Hesti Dwi Astuti; Moch Irfan Sofyan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The national energy transition toward renewable sources represents a strategic response to mounting ecological crises and high dependence on fossil fuels that negatively impact environmental sustainability. Indonesia holds substantial renewable energy potential; however, its realization remains constrained by various legal and institutional challenges. Normative aspects concerning energy and environmental protection are governed by Law Number 30 of 2007 on Energy and Law Number 32 of 2009 on Environmental Protection and Management. Nevertheless, the implementation of both regulations has not been fully effective due to inconsistencies among legal products, weak enforcement mechanisms, and inadequate supporting policies. This study employs a normative juridical approach with a descriptive-analytical character, drawing on regulatory reviews, environmental law theories, and sustainable development concepts. The findings indicate that green energy advancement in Indonesia is not yet undderpinned by an integrated and effectively functioning legal system. Moreover, the application of fundamental environmental law principles,including the precautionary principle, prevention principle, and sustainability,remains suboptimal. Therefore, regulatory synchronization, strengthened law enforcement capacity, and more responsive policy formulation are required to promote genuinely sustainable green energy development, provide legal certainty, and ensure environmental protection along with improved public